The Mindfulness in athletes and athletes (Revista de Investigaciones Universidad del Quindío, 2021)
Athletes are in constant training and education to develop and excel in different disciplines, this in turn requires great physical and psychological effort because must compete against each other countless times throughout their careers, thus creating in some way a constant pressure to “stand out” and “be the best”, resulting in equally constant stress. For this reason, it is necessary to carry out mindfulness sessions, which can vary in different techniques. Mindfulness seeks to impose the belief that it is necessary to change the usual emotions, sensations and thoughts that create this stress and athletes and athletes are taught to create a positive intention in order to improve their sports performance with an emphasis on thought control and the use of self-dialogue, this proposes relating one’s own internal states such as feeling and thinking in a different way, not trying to change or eliminate them, but taking them as a way of relating them to said states, this being called Mindfulness. Similarly, the application of mindfulness reduces the probability of presenting various psychological disorders, such as neuroticism, alexithymia, anxiety, depression, somatization, hostility, impulsivity, vulnerability to psychiatric diseases, addictions, aggressiveness and impulsivity.
Keywords: Mindfulness; emotions; athletes; positive experiences